Thermal Diffusivity Measurement of the Commercial Papers Using Photoacoustic Technique - Sheng, Chan Kok; Mat Yunus, W. Mahmood (Universiti Putra Malaysia Press, 2002)
We have carried out photo acoustic measurements of thermal diffusivity on samples of commercial papers. It is based upon the measurement of the photoacoustic signal as a function of the modulation frequency in the region where the sample thickness, t" was equal to the thermal diffusion length, If The value of the thermal diffusivities for the commercial papers was found to be adequate to their end users. It is also proven that the photoacoustic technique can be a valuable tool for comparing and controlling the properties of papers and for evaluating the effects of processing parameters upon these properties industrially or on the laboratory scale.